2017
DOI: 10.1002/2016jd025896
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of U.S. summer precipitation to model resolution and convective parameterizations across gray zone resolutions

Abstract: Simulating summer precipitation is a significant challenge for climate models that rely on cumulus parameterizations to represent moist convection processes. Motivated by recent advances in computing that support very high‐resolution modeling, this study aims to systematically evaluate the effects of model resolution and convective parameterizations across the gray zone resolutions. Simulations using the Weather Research and Forecasting model were conducted at grid spacings of 36 km, 12 km, and 4 km for two su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 77 publications
3
84
1
Order By: Relevance
“…Accurate downscaling of summer precipitation remains a great challenge for most mesoscale models (Gao et al, ; Liang et al, ; Qiao & Liang, ), even at convection‐allowing resolutions (Sun et al, ). Our previous dynamic downscaling of precipitation over the Great Plains for the past climate with the WRF model significantly underestimated warm‐season precipitation over the Southern Great Plains and shifted the band of maximum precipitation to the Rockies and Nebraska (Sun et al, ); in most cases, the rainband was shifted northwestward, regardless of convection‐allowing or convection‐parameterizing configurations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate downscaling of summer precipitation remains a great challenge for most mesoscale models (Gao et al, ; Liang et al, ; Qiao & Liang, ), even at convection‐allowing resolutions (Sun et al, ). Our previous dynamic downscaling of precipitation over the Great Plains for the past climate with the WRF model significantly underestimated warm‐season precipitation over the Southern Great Plains and shifted the band of maximum precipitation to the Rockies and Nebraska (Sun et al, ); in most cases, the rainband was shifted northwestward, regardless of convection‐allowing or convection‐parameterizing configurations.…”
Section: Methodsmentioning
confidence: 99%
“…Accurate downscaling of summer precipitation remains a great challenge for most mesoscale models (Gao et al, 2017;Liang et al, 2006;Qiao & Liang, 2015), even at convection-allowing resolutions (Sun et al, 2016).…”
Section: High-resolution Dynamic Downscaling Of August Climatementioning
confidence: 99%
“…These studies over land and another over the tropical Pacific (Holloway et al , 2012) concluded that the highest resolution simulations with convection explicitly resolved agreed best with observations. Similarly, Gao et al (2017) report improved representation of precipitation spatial distribution and timing in higher resolution (4 km when compared to 12 and 36 km). These results suggest that, at least for deep convection, we should expect better comparison to observations at higher resolution.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have mostly been conducted to either focus on fine spatial resolution over short durations or long duration at a coarse resolution (Chen & Hossain, ; Hu et al, ; Leung & Qian, ). With advances in computing resources, convection permitting climate simulations at grid spacing of a few kilometers are becoming feasible and recent studies have demonstrated their usefulness for simulating cold season orographic precipitation and snowpack dynamics (Rasmussen et al, ) and extreme precipitation (Liu et al, ; Prein et al, ) as well as warm season precipitation and its diurnal variability (Gao et al, ; Prein et al, ; Yang et al, ). Overcoming the limitations of both model resolution and simulation period opens the door to improving analysis of AR events on climate time scale.…”
Section: Introductionmentioning
confidence: 99%